2010
DOI: 10.1519/jsc.0b013e3181b2c7ff
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cost and Energy Sources During a Simulated Firefighting Activity

Abstract: This study aimed to 1) analyze the energy requirement (VO2eq) and the contribution of the aerobic (VO2ex), anaerobic alactic (VO2al), and anaerobic lactic (VO2la-) energy sources of a simulated intervention; 2) ascertain differences in mean VO2 and heart rate (HR) during firefighting tasks; and 3) verify the relationship between time of job completion and the fitness level of firefighters. Twenty Italian firefighters (age = 32 ± 6 yr, VO2peak = 43.1 ± 4.9 mL·kg·min) performed 4 consecutive tasks (i.e., child r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 42 publications
10
68
0
2
Order By: Relevance
“…Various studies [6,62,63] have determined that immersion in the smoke (search and rescue) is the most challenging task faced by the firefighters. Perroni et al [17] by analyzing simulated emergencies (i.e., child rescue; 250 m run; search and rescue; 250 m run) of 20 Italian firefighters have shown that VO 2 consumption of the search and rescue was 56 ± 6% compared to the total energy requirement of a simulated emergencies and was 67 ± 16% compared to VO 2max evaluated in laboratory.…”
Section: Cardiocirculatory Strainmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies [6,62,63] have determined that immersion in the smoke (search and rescue) is the most challenging task faced by the firefighters. Perroni et al [17] by analyzing simulated emergencies (i.e., child rescue; 250 m run; search and rescue; 250 m run) of 20 Italian firefighters have shown that VO 2 consumption of the search and rescue was 56 ± 6% compared to the total energy requirement of a simulated emergencies and was 67 ± 16% compared to VO 2max evaluated in laboratory.…”
Section: Cardiocirculatory Strainmentioning
confidence: 99%
“…HR increases during very hard work carried out for a shorter period of 15 min [9][10][11], and for a longer period [70], and remains high during the recovery phase [16,17]. Indeed, Perroni et al [17] showed that the values of HR and VO 2 increased during the simulated emergencies and they remained elevated after 30 Rodrıguez-Marroyoa et al [72] analyzed the HR of firefighters during real wildfire suppression according to the type of attack performed (direct, indirect or mixed). They found significantly higher HR in direct and mixed versus indirect attacks and demonstrated that wildfire firefighting depends on the tactics chosen for performing the task.…”
Section: Cardiocirculatory Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary α-amylase levels increase under stressful conditions known to increase plasma catecholamines [19][20][21][22]. The levels of α-amylase in the body have been used as an effective measure of stress, including social stress, such as performance in front of an audience [23][24][25], testing [26] ,competition [27,28], and physical stress [29][30][31]. Noninvasive measurement of activity in the SN system is also possible via skin conductance.…”
Section: Introductionmentioning
confidence: 99%